Application of the Extended Theory of Planned Behavior to Predict Exclusive Breastfeeding Intention, In Pregnant Nulliparous Women. A Cross-Sectional Study - Yazdanpanah, Farahnaz; Nasirzadeh, Mostafa; Ahmadinia, Hassan; Abdolkarimi, Mahdi (Investigación y Educación en Enfermería, 2022)
This study investigated the effect of Extended Theory of Planned Behavior (ETPB) extended theory of planned behavior in comparison with the Theory Of Planned Behavior (TPB) in explaining the intention of Exclusive Breastfeeding Intention (EBF) in Pregnant nulliparous women of Kerman (Iran). Methods. In this descriptive study, 249 pregnant women in Kerman participated via simple random sampling. The research instruments included Questionnaire related to the structures of the theory of planned behavior, breastfeeding self-efficacy and social support questionnaire for breastfeeding. Results. The results of the correlation test showed a significant relationship between all constructs of the theory of extended planned behavior and the intention of EBF. The highest correlation belonged to the construct of subjective norms (r=0.49). Path regression coefficients in the second model showed that the Self-Efficacy mediator variable is fully capable of meaningful mediation between Social Support and Intention (p<0.001; B=0.383). The conceptual diagram of Structural equation modeling showed a higher explained variance or R2 index for the intention variable for the developed model compared to that of the first model, i.e. (the first model: R2=0.37, the second model: R2=0.46). The goodness-of-fit index had a better status for the developed model. Conclusion. Extended TPB with social support and breastfeeding self-efficacy constructs can be appropriate model for predicting the intention and behavior of EBF.